The Utilization of Animation Media on Wortschatz Learning Outcomes and Motivation of Undergraduate Students of German Language - Yanti Arasi Sidabutar; Juni Agus Simaremare (Universitas Muhammadiyah Mataram, 2021)
The aim of the research was to see how effective learning media in terms of wortschatz learning outcomes and German students' motivation to learn. The research method used was, a quasi-experiment with One Group Pretest-Posttest. Essay tests and a motivation questionnaire are among the research instruments. The Researche use one quesetion for essay test and use twelve questions for motivation questionnaire. The showed that animation media can improve learning by increasing their wortschatz learning outcomes and motivation. This is shown by t-test results with sig. 0.000 and count -12.43. The application of animation media improves students' motivation to learn. with a sig. of 0.000, the gives a of -14.72.